Investigating heritage-led urban regeneration strategy for the historic district of Seremban - Ying, Chen Lit; Abu Bakar, Nor Azlina; Mohd Zairul (Human Resources Management Academic Research Society (HRMARS), 2024)
Due to accelerating urbanization and population growth, there is growing concern about how to regenerate deteriorated areas of old cities. Seremban's historic center currently exhibits various signs of urban degradation. A novel strategy for halting legacy deterioration and preserving the growth of historic cities is known as "heritage-led regeneration." However, within the context of redevelopment projects in Malaysia's historic cities, there is a lack of design requirements for a heritage protection strategy. This research aims to investigate historical conservation strategies to revive the dilapidated portion of Seremban's historical center. This study employs a qualitative approach, utilizing observation, desk review, and in-depth interviews to assess the need for a regeneration project and to propose an optimal heritage conservation plan for designing a regeneration project in Seremban's historical center. Additionally, the research will offer a design brief for a rehabilitation project in Seremban's historic district, contributing to making the area more livable and sustainably developed. Future studies may expand the scope of the design brief by incorporating additional variables to further enhance the heritage conservation and urban regeneration efforts.